Mobile direct-sequence spread-spectrum underwater acoustic communication based on improved differential energy detector - Peng-yu DU; Long-xiang GUO; Jing-wei YIN; Gang QIAO (Tongxin xuebao)
A Doppler estimation method based on the structural features of spread spectrum signal was proposed,which could achieve real-time Doppler estimation for received spread spectrum signals by energy detecting the result of matching correlation calculation of adjacent received spreading symbols.In addition,this method made full use of the spread spectrum processing gain and could do Doppler estimation under low SNR condition.Improved differential energy detector was further proposed,which can effectively deal with the rapid carrier phase fluctuation interference caused by Doppler effect and time-varying multi-path interference by detecting the output energy of two correlators.Simulation verified the robustness of improved differential energy detector algorithm and the Doppler estimation method based on spread spectrum signal.At-sea data shows that improved differential energy detector combined with the proposed Doppler estimation method can achieve low bit error rate communication for direct-sequence spread spectrum underwater acoustic communication with large time-varying Doppler interference when SNR is −10 dB.